Effect of broken skirts on voltage distribution along insulator strings - Othman, Nordiana Azlin; M. Piah, M. A.; Adzis, Z. (United Kingdom Simulation Society, 2016)
The existence of broken glass insulator as part of a complete string may alter the local voltage distribution. A finite element software is used to study the effect of broken glass insulator (stub) to the voltage distribution profile. In this paper we present the voltage distribution profile across single and ten units of glass insulator string with different locations. The results show that the presence of broken insulator under dry conditions and without contaminants affects the distribution profile of voltage. The local voltage distribution is certainly altered when the stub is present at any location in the string. However, maximum percentage increase in voltage is experienced when the stubs are located near to the ground (GND) end. This result helps to explain the ability of transmission line insulation system to operate satisfactorily even with the presence of stubs along the string.